The Age Structure of R&D Personnel as Factor of Ukraine’s Scientific System Viability - Popovych, O.S.; Kostrytsa, O.P. (Science and Innovation, 2024)
The dynamics of age structure of scientific personnel in Ukraine for the period from 1995 to 2014 have been analyzed. The age profiles of researchers in Ukraine and Russia has been compared. A new trend in the national science has been identified: since 2005, while the average age increasing, the share of researchers aged 30–39 years has been growing and reached 22%, in 2014 (at the same time, the youngest age group of under 29 accounted for 37%). This means that the concept of "total aging" and the resulting loss of productivity of Ukrainian science is too simplified to mirror the existing situation, and confirms that the current age structure of scientific personnel is still able to ensure a rapid improvement of capacity if the government provides support in effective manner.